SERVICE QUALITY IN MALINDI’S TOURISM INDUSTRY - WANJOHI KIBICHO (Centre For Tourism Planning and Development, 2006)
This study is an attempt to investigate the tourism service quality in Malindi, Kenya. It is based on a fieldwork research carried out in October through December 2000. SERVQUAL model was used in generation of questionnaires which were the primary tools for data collection. The study results suggest that, the performance-based measures of service quality can be used to provide an index of the quality perceptions of a tourist destination’s service providers. It provides insightful and meaningful information about tourists’ perceptions of a particular service. This study, for instance, found that beach operators, informal micro-entrepreneurs, play an important role in the overall tourism service quality in Malindi.